Bir gʻazali tahlili: "Tishni sinkim dedilar..." - Rayhonoy Yangiboyeva (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
In this article, the orifona ghazal from the "Navodir ush shabab" divan of His Holiness Navoi is analyzed. The poet's ability to reflect the deep philosophical content based on a life event and to express it with a mystical tone is revealed. An attempt was made to explain the meaning of the required words in the commentary.